2017
DOI: 10.5539/ass.v13n2p49
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the E-book on Levels of Bloom's Pyramid at ECT Students in Light of the Internal and External Motivation to Learn Mathematics and Statistics

Abstract: The purpose of the present study was to examine the effects of E-book of the Pyramid Bloom levels on the Emirates College of Technology (ECT) students at both internal and external motivation levels. The business statistics unit developed in two different methods. This study utilized the quasi experimental type methodology. The independent variables were the methods, traditional and E-book. The dependent variables were the Pyramid Bloom levels, which will be determined by the final mark on the post-test. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The results obtained demonstrated that the use of mathematics e-books positively impacts students' mathematics achievement. This finding is in line with previous research that stated mathematics e-books also has a positive effect on students' mathematical skills [ 29 , 33 , 60 ]. One of the advantages of mathematics e-books is its ability to enhance students’ numerical ability and provide an interactive learning environment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results obtained demonstrated that the use of mathematics e-books positively impacts students' mathematics achievement. This finding is in line with previous research that stated mathematics e-books also has a positive effect on students' mathematical skills [ 29 , 33 , 60 ]. One of the advantages of mathematics e-books is its ability to enhance students’ numerical ability and provide an interactive learning environment.…”
Section: Discussionsupporting
confidence: 93%
“…This meta-analysis research aims better to understand the effect of e-books on students' mathematics achievement. Mathematics e-books have been adopted at the pre-school [ 57 ], elementary [ 32 ], secondary [ 58 ], and university levels [ 33 ]. In addition, they also trigger and motivate students to learn mathematics [ 19 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we know that the information technology and the means of communication and technology of education in our lives has become an integral part of that revolution (Aldalalah, 2018). So the computer has had a significant role in increasing the speed of moving the wheel of life significantly, Educational institutions should take benefits from computer data in order to keep abreast of the rapid development around them (Shatat, Aldalalah &. Ababneh, 2017).…”
Section: Augmented Realitymentioning
confidence: 99%